Inhibition of BATF/JUN transcriptional activity protects against osteoarthritic cartilage destruction - Rhee, Jinseol (Ann Rheum Dis, 2017)
OBJECTIVE: The basic leucine zipper transcription factor, ATF-like (BATF), a member of the Activator protein-1 family, promotes transcriptional activation or repression, depending on the interacting partners (JUN-B or C-JUN). Here, we investigated whether the BATF/JUN complex exerts regulatory effects on catabolic and anabolic gene expression in chondrocytes and contributes to the pathogenesis of osteoarthritis (OA). METHODS: Primary cultured mouse chondrocytes were treated with proinflammatory cytokines (interleukin-1β, IL-6 or tumour necrosis factor-α) or infected with adenoviruses carrying the Batf gene (Ad-Batf). Expression of BATF and JUN was examined in human and mouse experimental OA cartilage samples. Experimental OA in mice was induced by destabilisation of the medial meniscus or intra-articular injection of Ad-Batf. The chromatin immunoprecipitation assay was used to examine the binding of BATF and JUN to the promoter regions of candidate genes. RESULTS: Overexpression of BATF, which forms a heterodimeric complex with JUN-B and C-JUN, induced upregulation of matrix-degrading enzymes and downregulation of cartilage matrix molecules in chondrocytes. BATF expression in mouse joint tissues promoted OA cartilage destruction, and conversely, knockout of Batf in mice suppressed experimental OA. Pharmacological inhibition of BATF/JUN transcriptional activity reduced the expression of matrix-degrading enzymes and protected against experimental OA in mice. CONCLUSIONS: BATF/JUN-B and BATF/C-JUN complexes play important roles in OA cartilage destruction through regulating anabolic and catabolic gene expression in chondrocytes. Our findings collectively support the utility of BATF as a therapeutic target for OA.